Knowledge graph and semantic computing : semantic, knowledge, and linked big data : first China Conference, CCKS 2016, Beijing, China, September 19-22, 2016, Revised selected papers /: semantic, knowledge, and linked big data : first China Conference, CCKS 2016, Beijing, China, September 19-22, 2016, Revised selected papers. (2016) - Unknown
No abstract available